Influencia del marketing estratégico en la internacionalización asociativa. - Guanaquiza, Michelle; Mideros, Victor; Micolta, Patricia; Sánchez González, Irene (My University, 2021)
Analyze the influence of strategic marketing and the associativity of companies, as a tool for internationalization. The descriptive-probabilistic method is used, with a cross-sectional approach, applying a structured questionnaire to a sample of 400 managers of associations in the province of El Oro. Strategic marketing and marketing cooperation have a high level of influence on companies that associate to internationalize. Associations that cooperate with each other, and that implement strategic marketing efforts in their operations, have greater positive results to internationalize their products.
Analizar la influencia del marketing estratégico y la asociatividad de las empresas,como herramienta para la internacionalización.Se utiliza el método descriptivo - probabilístico, con enfoque transversal aplicando un cuestionario estructurado a una muestra de 400 gerentes de asociaciones de la provincia de El Oro. El marketing estratégico y la cooperación de marketing, tienen un alto nivel de influencia sobre las empresas que se asocian para internacionalizarse. Las asociaciones que cooperan entre sí, y que implementan gestiones de marketing estratégico en sus operaciones, tienen mayores resultados positivos para internacionalizar sus productos.
Keywords: MARKETING ESTRATÉGICO; COOPERACIÓN DE MARKETING; INTERNACIONALIZACIÓN; ASOCIATIVIDAD; ASOCIACIONES